Perturbed eigenvalue problems: an overview - FĂRCĂȘEANU, Maria; GRECU, Andrei; MIHĂILESCU, Mihai; STANCU-DUMITRU, Denisa (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
The study of perturbed eigenvalue problems has been a very active field of investigation throughout the years. In this survey we collect several results in the field. Mathematics Subject Classiffication (2010): 35D30, 35D40, 46E30, 49J40, 35A15.